1979
DOI: 10.1038/281689a0
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic acid inhibits virus growth and inactivates virus particles

Abstract: Screening investigations in antiviral action of plant extracts have revealed that a component of Glycyrrhiza glabra roots, found to be glycyrrhizie acid, is active against viruses. We report here that this drug inhibits growth and cytopathology of several unrelated DNA and RNA viruses, while not affecting cell activity and ability to replicate. In addition, glycyrrhizic acid inactivates herpes simplex virus particles irreversibly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
254
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(259 citation statements)
references
References 4 publications
3
254
0
2
Order By: Relevance
“…It has in-vitro and in-vivo antiviral activity, interfering with DNA and RNA replication of a wide range of viruses, including herpes, influenza A and B, hepatitis B, coronavirus, and SARS (Pompei, et al, 1979;Hirabayashi et al, 1991;Badam, 1994;Lin, 2003;Hoever, et al 2005;Lee, et al, 2007). This pharmaceutical preparation has also been demonstrated to be able to prevent the virion from hatching from its capsid (Pompei, et al, 1979;Lin, 2003), apparently due to a dose-dependent inhibition of kinase-P phosphorylation (Chavali, et al, 1987;Ohtsuki and Ishida, 1988). In addition, GRA has been shown to interfere with arylamine N-acetyltransferase bacterial activity, thereby exhibiting antibacterial effects, at least against Streptococcus spp., Haemophilus spp., and Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…It has in-vitro and in-vivo antiviral activity, interfering with DNA and RNA replication of a wide range of viruses, including herpes, influenza A and B, hepatitis B, coronavirus, and SARS (Pompei, et al, 1979;Hirabayashi et al, 1991;Badam, 1994;Lin, 2003;Hoever, et al 2005;Lee, et al, 2007). This pharmaceutical preparation has also been demonstrated to be able to prevent the virion from hatching from its capsid (Pompei, et al, 1979;Lin, 2003), apparently due to a dose-dependent inhibition of kinase-P phosphorylation (Chavali, et al, 1987;Ohtsuki and Ishida, 1988). In addition, GRA has been shown to interfere with arylamine N-acetyltransferase bacterial activity, thereby exhibiting antibacterial effects, at least against Streptococcus spp., Haemophilus spp., and Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that GL has various biological activities, such as an anti-inflammatory effect, 1) an anti-viral effect, 2) interferon-g-inducing activity, 3) and the ability to induce extrathymic T cells. 4) Recently, we reported that (i) three phospholipases A 2 (PLA 2 s) [PA2Y (Tf PL-X, 121 amino acid residues), PA21 (Tf PLA, 122 amino acid residues) and PA2B (lysine-49-PLA 2 , 122 amino acid residues)] are selectively purified from Habu snake venom as GL-binding proteins (gbPs); and (ii) PA2B is a GL-sensitive enzyme in vitro.…”
mentioning
confidence: 99%
“…2) Licorice root is one of the most frequently used crude drugs in Kampo medicine. 3) Its active ingredient is GL, which has been reported to show various pharmacological effects such as steroid-like, 4) anti-inflammatory, 5) and anti-viral 6) actions. On the other hand, GL is known to be hydrolyzed to glycyrrhetic acid (GA), the aglycone of GL, by human intestinal bacteria prior to absorption, 7) although GL is not hydrolyzed to GA, but to glycyrrhetic acid mono-glucuronide (GAMG), by human liver b-D-glucuronidase.…”
mentioning
confidence: 99%